1995
DOI: 10.1172/jci117675
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene transcription of angiotensin II receptor subtypes in myocardial infarction.

Abstract: Increasing evidence suggests that angiotensin II (AngHI) acts as a modulator for ventricular remodeling after myocardial infarction. Using competitive reverse-transcriptase polymerase chain reaction, nuclear runoff, and binding assays, we examined the regulation of AngHI type la and lb (ATla-R and ATlb-R) and type 2 receptor (AT2-R) expression in the infarcted rat heart as well as the effects of AngiH receptor antagonists. ATla-R mRNA levels were increased in the infarcted (4.2-fold) and noninfarcted portions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
238
7
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(263 citation statements)
references
References 52 publications
14
238
7
4
Order By: Relevance
“…The highly abundant expression of AT 2 receptor during embryonic and neonatal growth, the rapid disappearance after birth (4,6), and the up-regulation of AT 2 receptor in myocardial infarction (27), cardiac hypertrophy (28), and skin wound (29) suggest that this receptor is closely involved with growth, development, and/or differentiation. Dudley et al (14) reported that the addition of growth factors, such as basic fibroblast growth factor or serum, to quiescent R3T3 cells caused a rapid decrease in the number of surface AT 2 receptor sites.…”
Section: Discussionmentioning
confidence: 99%
“…The highly abundant expression of AT 2 receptor during embryonic and neonatal growth, the rapid disappearance after birth (4,6), and the up-regulation of AT 2 receptor in myocardial infarction (27), cardiac hypertrophy (28), and skin wound (29) suggest that this receptor is closely involved with growth, development, and/or differentiation. Dudley et al (14) reported that the addition of growth factors, such as basic fibroblast growth factor or serum, to quiescent R3T3 cells caused a rapid decrease in the number of surface AT 2 receptor sites.…”
Section: Discussionmentioning
confidence: 99%
“…8 -10 Many studies have demonstrated that hemodynamic overload activates the tissue RAS in the heart. [11][12][13][14][15][16] mRNA and/or protein levels of renin, 11 ACE, 12,13 angiotensinogen, 5,11,14 and Ang II receptors 15,16 have been reported to be increased in hypertrophied hearts. In addition to these in vivo studies, mechanisms by which mechanical stress induces cardiomyocyte hypertrophy have also been investigated in vitro with cultured cardiac myocytes.…”
mentioning
confidence: 99%
“…For example, an increase in AT1R density has been reported in the heart after myocardial infarction (17,18) and in hearts from biopsies from patients with spontaneous intracerebral hemorrhage (19). Several cytokines, such as tumor necrosis factor (TNF)-␣ and interleukin (IL)-1␤, have been reported to up-regulate AT1R (17,20).…”
Section: Ptxmentioning
confidence: 98%